ATRT-08. IDENTIFYING AND ACCELERATING POTENTIAL NEW DRUG THERAPIES FOR PEDIATRIC ATYPICAL TERATOID RHABDOID TUMORS (ATRTs) THROUGH DRUG REPURPOSING. Issue 2 (22nd June 2018) - Wood, Nicole; Ginn, Kevin; Roy, Anuradha; Huntley, Coral; Weir, Scott; Ramamoorthy, Prabhu; Anant, Shrikant
Abstract: CNS ATRTs are rare, aggressive tumors occurring in very young children and have a poor prognosis and high morbidity. Even with aggressive multi-modal therapy, the cure rate remains less than 50%. New therapy approaches are desperately needed. The broad objective of this project is to accelerate new treatments for ATRT by employing drug repurposing strategies. A high throughput screening (HTS) assay was developed to interrogate our curated library of FDA-approved and industry-abandoned drugs. Two ATRT cell lines from the Children's Oncology Group were used for the primary HTS. 3, 574 FDA-approved and abandoned drugs were screened using a well-established CellTiter-Glo® Luminescent Cell Viability Assay to determine drug effect on ATRT cell line viability and 122 active drugs were identified. Based on demonstrated systems pharmacology data, drug development and regulatory science considerations, and the ability of agents to cross the blood brain barrier, 9 drugs were selected for in vitro studies. Drug effects on cell proliferation, colony formation, spheroid formation, cell cycle, migration, invasion, and cell signaling pathways will be characterized in human control and ATRT cell lines. Based on resulting mechanistic data, in vitro combination studies will be conducted to determine additive or synergistic anticancer activity in the ATRT cell lines. Building upon our extensive track record of advancing 12 repurposed FDA-approved drugs to cancer experimental therapeutics clinical trials over the past seven years, we will employ innovative drug development and regulatory science strategies to rapidly translate promising new treatments identified through this research to ATRT patients.